Shelf life of frozen desalted cod (Gadus morhua) ... - Dargentolle, Cecile; Sveinsdóttir, Hildur Inga; Baldursson, Jónas; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
Þessi skýrsla er lokuð / This report is closed. ...